Determining the Impact of Prenatal Tobacco Exposure on Self-regulation at Six Months - Wiebe, Sandra A. (2014)
The goal of the present study was to examine the effects of maternal smoking during pregnancy on infant self-regulation, exploring birth weight as a mediator and sex as a moderator of risk. A prospective sample of 218 infants was assessed at 6 months of age. Infants completed a battery of tasks assessing working memory/inhibition, attention, and emotional reactivity and regulation. Propensity scores were used to statistically control for confounding risk factors associated with maternal smoking during pregnancy. After prenatal and postnatal confounds were controlled, prenatal tobacco exposure was related to reactivity to frustration and control of attention during stimulus encoding. Birth weight did not mediate the effect of prenatal exposure, but was independently related to reactivity and working memory/inhibition. The effect of tobacco exposure was not moderated by sex.